Genotoxicity, haematological and growth performance of the African catfish Clarias gariepinus fingerlings fed walnut Tetracarpidium conophorum leaves to substitute for rice bran - Simeon Oluwatoyin Ayoola; Adebola Afolashade Bamiro (Aceh Journal of Animal Science, 2017)
A plant has become a preferred source of protein for fish species in aquaculture. A twelve-week feeding trial was carried out in order to assess the effect of feeding walnut leaves on haematological and biochemical parameters as well as the genotoxicity level on Clarias gariepinus fingerlings as a bio-indicator of their health status and overall response of the fish towards the experimental diets. One hundred and fifty fingerlings of Clarias gariepinus of mean weight 6.90±0.2g were stocked randomly as ten fish per tank (52.5 X 33.5 X 21 cm3) in triplicate. Fish were fed to satiation and the water changed every day to maintain good water quality. Five experimental diets with 40% crude protein each were formulated; the control, without the test ingredient and the other four diets (test diets1, 2, 3 and 4) contained 25%, 50%, 75% and 100% inclusion respectively. The Control diet had the highest mean weight gain (P < 0.05) (118.8±17.3) among the entire group. A similar pattern was observed in specific growth rate. The least significant (P < 0.05) feed conversion ratio was recorded by the Control diet(0.68±0.03), the diet also recorded the best protein efficiency ratio (3.53±0.23).The genotoxicity test shows that some Micronucleus of the test diets were normal, lobed and binucleated nucleus compared to the Control diet. The fish fed with T. conophorum showed a significant difference in haematological values when compared to the values of fish fed the control diet. The fish fed with T. conophorum showed a significant difference in biochemical value when compared with control diet. There was a reduction in the biochemical values of the fish fed T. Conophorum with Cholesterol (2.20±0.05) Albumin (8.35±0.21) and Triglyceride (0.98±0.13) compared with the values of fish fed with the control diet with cholesterol (3.81±0.07) Albumin (12.35±2.33) and Triglyceride (7.29±7.02). It was concluded that using T. Conophorum leaves as feed for Clarias gariepinus enhances the growth of the fish. Therefore, partial replacement of feed T. Conophorum should be encouraged.